2017
DOI: 10.1016/j.molcel.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Transport of Glutathione by Sec61 Is Regulated by Ero1 and Bip

Abstract: In the endoplasmic reticulum (ER), Ero1 catalyzes disulfide bond formation and promotes glutathione (GSH) oxidation to GSSG. Since glutathione cannot be reduced in the ER, maintenance of the ER GSH redox state and levels likely depend on ER GSH import and GSSG export. We used quantitative GSH and GSSG biosensors to monitor GSH import into the ER of yeast cells. We found that GSH enters the ER by facilitated diffusion through the Sec61 protein-conducting channel, while oxidized Bip (Kar2) inhibits transport. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 51 publications
1
114
0
Order By: Relevance
“…However, a recent study shows that transport of glutathione from cytosol to ER proceeds via facilitated diffusion through Sec61 in a coupling system with Ero1 and Bip [157].…”
Section: Endoplasmic Reticulum Glutathionementioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study shows that transport of glutathione from cytosol to ER proceeds via facilitated diffusion through Sec61 in a coupling system with Ero1 and Bip [157].…”
Section: Endoplasmic Reticulum Glutathionementioning
confidence: 99%
“…Also, it was suggested that GSH is preferentially transported into the ER, compared to GSSG, and that this transport takes place in an energy‐independent manner . However, a recent study shows that transport of glutathione from cytosol to ER proceeds via facilitated diffusion through Sec61 in a coupling system with Ero1 and Bip .…”
Section: Subcellular Compartmentalizationmentioning
confidence: 99%
“…A reasonable explanation for this permeability may be found in the translocon channel (Sec61 complex) which enables the co-and post-translational transport of proteins into the ER (Osborne, Rapoport & van den Berg, 2005;Gogala et al, 2014;Dudek et al, 2015;Pfeffer et al, 2015) but may also allow the rather non-specific passage of other molecules (Csala et al, 2007). Intriguingly, a recent study in yeast, shows that glutathione can enter the ER via facilitated diffusion through Sec61, along a concentration gradient (Ponsero et al, 2017). To return to ER ATP transport, it seems plausible then that ATP could diffuse through the translocon channel during protein translocation.…”
Section: (5) a General Perspective On Er Transportmentioning
confidence: 99%
“…As discussed in Guerrero-Gómez et al (2018), neither thioredoxin nor glutathione redox systems representatives were found in the ER, and the identity of the enzymatic systems providing reducing equivalents to ER-resident PDIs remained elusive for long time. The current model implies that cytoplasmic thioredoxin shuttles electrons into the ER to reduce oxidized PDIs (Poet et al 2017), while GSH is actively transported from cytoplasm by specific transporters (Ponsero et al 2017). Along the protein traverse across the secretory pathway, it is subjected to further specific modifications, multiple quality-control points, and sorting to finally reach the destination site.…”
Section: General Overview Of the Canonical Protein Secretion Pathwaymentioning
confidence: 99%